Application of Father's Song Arrangement "Rinto Harahap" in School Music at SMKN 1 Padangpanjang - Zulkarnain, Zulkarnain; Yusnelli, Yusnelli; Rosmegawaty, Rosmegawaty; Awerman, Awerman; Syahputra, Ade (Scoring: Journal of Film Music, 2024)
The song Ayah was created by Rinto Harahap. This song originates from the motivation of a child who is far from his father figure to seek knowledge and a future. This song was re-arranged by Albiner Purba, S.Sn for final work research in the form of a mixed ensemble which will be applied to students at SMKN 1 Padang Panjang. This ensemble uses musical instruments including Keyboard, Cajon, Acoustic Guitar, Bass Guitar, Pianica, Flute, and Vocals. There are 8 players in this musical ensemble, consisting of 5 men and 3 women. This research is qualitative and descriptive in nature, with an action research design approach and applying supporting methods: lectures, demonstrations, exercises, experiments, and evaluations. This research also uses data analysis techniques: searching and compiling data, organizing data, selecting data, and analyzing data. The results of this research show students' progress and knowledge in ensemble playing: they can regulate dynamics, tempo, discipline in playing, and play song material using instruments well and correctly. Apart from that, this research succeeded in realizing the achievements of the SMKN 1 Padangpanjang school curriculum, namely implementing sustainable practice habits and producing main ideas which were then directed to the presentation of musical works.